PENGARUH PENAMBAHAN BERBAGAI JENIS BAHAN SERAT TERHADAP KUALITAS ETERNIT - A. Manap , Darmono (Universitas Negeri Yogyakarta, 2010)
ABSTRACTAddition of fibres obtained from waste of projects and home industries can beperformed in the fabrication of plasterboard as an effort to produce multiple benefitsand to optimize its ulitization This research was an experimental research consists of1 independent variable, which was the composition of Portland cement (SM), mill chalk(KM), and rosella (SR) mixture in 5 different compositions. Those were I(1 SM : 5 KM :0,06 SR), II( 1 SM : 5 KM : 0,08 SR), III(1 SM : 5 KM : 0,10 SR ), IV(1 SM : 5 KM : 0,12SR ), and V(1 SM : 5 KM : 0,14. SR), each of the composition was repeated threetimes. Mixing of material and plasterboard fabrication were done manually. Type oftesting were the observation of shape/visually and plasterboard weight, measurementof length, width and thickness, easiness with nails and placing, water absorbtion, waterdensity, mass per volume, and flexural strength. To investigate the real effect ofindependent variable to each parameter, the observation was conducted as dataanalysis using single line anava test dan DMRT test. The result showed that (1)Composition II (1:5:0,08) was one with good result on the observation ofshape/visually, measurement of length, width and thickness, easiness with nails andplacing, water absorbtion, water density, and mass per volume of plasterboard. (2)Composition of rosella fibre mixture gave bad effect to flexural bending of plasterboard.The test result on easiness showed that composition placed well on seven days of agewere the ratio 1:5:0,10; dan 1:5:0,12. (3) Comparison of physical and mechanicalaverage value showed that composition II (1:5:0,08.) was the best ratio. There results ifcompared to Indonesian Standard for Industry, Standar Industri Indonesia (SII.0016-72) about cement fibre sheet were complied for observation of shape/visually,measurement of length, width and thickness, easiness with nails and placing, waterabsorbtion, water density, mass per volume, while for the flexural strength none werecomplied.Keywords: fibre, plasterboard and mixture composition